Testotoxicosis: gonadotrophin-independent male sexual precocity. - Aziz, A. A. (BMJ Group, 1992)
In this era of rapidly developing investigational tools and pharmacology, the pathophysiology of precocious puberty is becoming well defined. What was previously thought to be a form of gonadotrophin releasing hormone (GNRH)-dependent central precocious puberty is now classified as GNRH-independent familial testotoxicosis. We present two such cases and review the clinical features, pathophysiology and treatment of testotoxicosis.